RELATIONSHIPS AMONG EVENT QUALITY, ATHLETE SATISFACTION AND FUTURE PARTICIPATION IN UNIVERSITY SPORTS EVENTS (Journal of Event, Tourism and Hospitality Studies, 2025)
This study investigates the influence of event quality specifically facilities and support services on athletes’ satisfaction and future participation to the event during the SUKIPT 2024 sports event hosted at Universiti Utara Malaysia (UUM). The primary objective is to evaluate how these elements of event quality affect athlete experiences and their intention for future participation to the event. Using a quantitative research design, data were collected through purposive sampling via a structured questionnaire administered to 233 athletes who directly engaged with the event’s facilities and services. Statistical analyses, including regression and correlation, were conducted using SPSS Version 30. Results reveal that both facilities (β = 0.662, p < 0.001) and support services (β = 0.216, p = 0.021) significantly predict athlete satisfaction, explaining 75.4% of the variance. Moreover, a strong positive correlation (r = 0.929, p < 0.001) was found between athlete satisfaction and future participation to the event, highlighting that improved event quality can substantially enhance athletes’ loyalty and willingness to return. This study makes a meaningful contribution to sports event management by empirically validating the link between event quality dimensions and athlete outcomes in a university sports context. The findings offer actionable recommendations for event organizers to improve facilities, logistics and service delivery ultimately supporting the sustainability and success of inter-university sports events in Malaysia.